Exploiting online social gambling for marketing communications. (3rd April 2018) - Ozuem, Wilson; Prasad, Jason; Lancaster, Geoff
Abstract: Internet technology provides a new approach to how gambling is conducted in postmodern times. Drawing on constructivist research and utilising a single case study strategy, this paper examines online social gambling and real money gambling marketing communication practices, as well as offering some insights into the development and implementation of effective marketing communication programmes. In contrast to existing studies, this paper, in part, proposes integrative and higher levels of marketing communication programmes between online social gambling and real money gambling environments. The paper reveals the implicit structure of meanings underlying the link between online social gambling activity and real money gambling practices.